Criteria of ideal english language teachers as perceived by secondary and tertiary Indonesian students - Md Zamin, Ainul Azmin; Salam, Nur; Tundung Subali Patima, Patima; Aulia Nourma, Putri; Abd Latif, Azmi (Universiti Tun Hussein Onn Malaysia Publisher’s Office, 2020)
This study presents English teachers' professional, personality, social, leadership, and classroom interaction attributes which senior high school and university students expect from their English teachers. By knowing those attributes, English teachers are expected to be able to help their students attain better English language proficiency. For the investigation, five sets of questions were distributed in order to find out the respondents’ favourite English teachers attributes. The respondents consisted of senior students of three high schools and undergraduates of three universities who had high, mediocre and low English language proficiency. The results show that the students' levels of education and English language proficiency influence the students' perceptions on their English teachers' attributes. This study suggests that English teachers recognize the attributes that their students highly expect from them. It is suggested that English teacher training institutions should conduct more professional English language and language teaching trainings that help teachers to develop the attributes. It is also suggested that the Ministry of Research, Technology and Higher Education of the Republic of Indonesia to monitor and evaluate universities and institutions which establish English Education Departments.